2015
DOI: 10.1093/ijnp/pyv019
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Mediates Pain-Induced Anxiety through the ERK1/2 Signaling Cascade in Locus Coeruleus Neurons

Abstract: Background:The corticotropin-releasing factor is a stress-related neuropeptide that modulates locus coeruleus activity. As locus coeruleus has been involved in pain and stress-related patologies, we tested whether the pain-induced anxiety is a result of the corticotropin-releasing factor released in the locus coeruleus.Methods:Complete Freund’s adjuvant-induced monoarthritis was used as inflammatory chronic pain model. α-Helical corticotropin-releasing factor receptor antagonist was microinjected into the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The development of anxio-depressive-like behaviors in chronic pain animal models has been reported in several studies [9,10,12,13,48]. Previous studies from our group have shown that anxiety-like behaviors in the CFA monoarthritis model are already present at 28 days [9,10,12].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The development of anxio-depressive-like behaviors in chronic pain animal models has been reported in several studies [9,10,12,13,48]. Previous studies from our group have shown that anxiety-like behaviors in the CFA monoarthritis model are already present at 28 days [9,10,12].…”
Section: Discussionmentioning
confidence: 52%
“…The pathophysiological mechanisms underlying pain, in these chronic conditions, are still not completely understood [4][5][6][7][8].Chronic pain involves many different complex processes in key spinal and supraspinal areas, which may suffer significant changes in an attempt to adapt to the ongoing noxious stimuli [4,5,7]. Indeed, the control of pain implies several molecular changes at the spinal cord, in the descending modulation of pain, and in supraspinal areas involved in the emotional component of pain processing [4,5,7,[9][10][11]. The latter may be influenced and altered by the noxious stimuli and also may be responsible for changes in the way these pathologic stimuli are processed [9,12,13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In an inflammatory chronic pain model (complete Freund's adjuvant‐induced monoarthritis model), the microinjection of CRF in the LC has been reported to cause nociceptive and anxiety‐like behaviors, while increasing the levels of phosphorylated extracellular signal‐regulated kinases 1/2 in both the LC and paraventricular nucleus, although the expression of CRF receptors remained unaltered. These findings suggest that, after inflammatory pain, pain‐induced anxiety is mediated by CRF neurotransmission in the LC through extracellular signal‐regulated kinases 1/2 signaling cascade (Borges et al, ) (Fig. ).…”
Section: Plasticity In Brainstem Structures Associated With the Modulmentioning
confidence: 83%